Diagnostics of the Level of Readiness of Older Teenagers to Independent Life under the Conditions of Family-Type Children's Communities - Tetiana Loza (Pedagogical Discourse, 2014)
Education experience of children-orphans under the family conditions proves the topicality of study of different aspects of preparation of such pupils to independent life as soon as they reach older teen age. Based on empirical research in this article we have presented the indicators of readiness of pupils of family-type children's communities to independent living by the following criteria: readiness to family life, social competence and professional readiness. The results of the conducted diagnostics allow us to come to the conclusion about the following characteristics of the pupils: individual psychological characteristics, role expectations and demands, typical kinds of behavior in the group; behavioral stereotypes and conceptions about the family relationships, correspondence of social age to chronological one, peculiarities of self- actualization, level of civil socialization, state of readiness of the system of term values, the level of professional motivation, the character of emotional attitude to the process of professional formation, accordance of the available abilities to the respondents’ inclinations. Based on the author’s interpretation of the received indicators the conclusion about the necessity of developing the forms and methods of purposeful social-pedagogical support of these pupils as soon as they are of older teen age to rise the effectiveness of their preparation to self-realization in different spheres of their independent life.